2013
DOI: 10.1063/1.4824214
|View full text |Cite
|
Sign up to set email alerts
|

Resistive switching artificially induced in a dielectric/ferroelectric composite diode

Abstract: Ferroelectric resistive switching was artificially induced in a conductive ferroelectric capacitor by inserting a thin dielectric layer at an electrode/ferroelectric interface. Ferroelectric capacitors consisting of semiconducting Bi-deficient Bi1−δFeO3 layers with SrRuO3 electrodes showed no resistive switching, but resistive switching emerged in these ferroelectric capacitors when a thin LaFeO3 dielectric layer was inserted at one of the SrRuO3/Bi1−δFeO3 interfaces. In addition to resistive switching, SrRuO3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
27
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(28 citation statements)
references
References 31 publications
1
27
0
Order By: Relevance
“…The first of these effects is imperfect charge screening, as described by a finite screening length λ eff , i.e., by band bending in an electrode . The second effect is the presence of a dead layer in the ferroelectric barrier, creating an asymmetric potential distribution through formation of a depolarization field . In the Co/BTO( A )/LSMO junction (Figure a), we consider practically perfect charge screening ( λ eff ≈ 0) and a zero thickness of the dead layer at the Co/BTO( A ) interface, as predicted theoretically .…”
Section: Discussionmentioning
confidence: 95%
“…The first of these effects is imperfect charge screening, as described by a finite screening length λ eff , i.e., by band bending in an electrode . The second effect is the presence of a dead layer in the ferroelectric barrier, creating an asymmetric potential distribution through formation of a depolarization field . In the Co/BTO( A )/LSMO junction (Figure a), we consider practically perfect charge screening ( λ eff ≈ 0) and a zero thickness of the dead layer at the Co/BTO( A ) interface, as predicted theoretically .…”
Section: Discussionmentioning
confidence: 95%
“…[8][9][10] It is generally accepted that the asymmetry of FTJs plays a key role for the orientation of a sizable TER, such as using asymmetric electrodes [11][12][13][14][15][16][17] or constructing asymmetric metal/FE interfaces. [18][19][20][21][22][23][24][25][26][27] Indeed, the sizable TER effect had been observed in several BaTiO 3 (BTO) based asymmetric FTJs experimentally. For example, Soni et al 16 observed giant TER effect in La 0:7 Sr 0:3 MnO 3 (LSMO)/BTO/Au and LSMO/BTO/Cu asymmetric FTJs owing to effective potential barrier modulation by the polarization.…”
mentioning
confidence: 99%
“…The structural and/or electronic asymmetry of the FTJ plays a decisive role for the TER effect. It can be achieved using dissimilar electrodes [9,[19][20][21][22], through interface engineering [13,[23][24][25][26], or applied bias [27,28]. Additionally, using ferromagnetic electrodes in a FTJ adds functionality, forming a multiferroic tunnel junction (MFTJ) [29].…”
Section: Introductionmentioning
confidence: 99%